(untitled) - Rampa, Giorgio (New York, 1998)
Sir Roy Harrod was one of the foremost economists of the 20th century who made pioneering contributions in several branches of economics including: trade cycle theory; growth theory; trade theory; monetary economics; imperfect competition theory; and methodology. This volume arises out of a conference to celebrate the sixtieth anniversary of the publication of his book The Trade Cycle in 1936. After introductory essays by Walter Eltis, a student of Harrod, the volume contains important essays on the interpretation of Harrod's work in the fields of economic dynamics, trade and growth, and his views on trade theory, international monetary reform and inflation.
Keywords: Harrod, Roy Forbes, Sir, 1900-,Business cycles,Economic development,Statics and dynamics (social sciences)